Avaliação da citotoxicidade do composto de inclusão de erlotinibe em hidroxipropil-beta-ciclodextrina e da hipertermia associada à cisplatina - Savio Morato de Lacerda Gontijo (2015)
Strategies widely used to potentiate the cytotoxic effects of antitumor molecules with the aim of reduce the applied dose and side effects are molecular inclusion and the combination of chemotherapy with hyperthermia. In this thesis, these two strategies were studied, the first molecular inclusion that is widely used to enhance solubility, absorption and availability molecules; and the second, hyperthermia which is a proposal for treatment of cancer where the tumor cells are affected by local temperature elevation and can be associated with chemotherapy to enhance the effects of this technique. For molecular inclusion used to hydroxypropyl--cyclodextrin (HP--CD) to enhance solubility, absorption and availability of erlotinib (ERL), was characterized physicochemicallyand evaluated the in vitro cytotoxicity and apoptosis, and in vivo inflammatory angiogenesis in Swiss mice. To evaluate the cytotoxic ofhyperthermia (heating to 42°C or 43°C for 1h) associated with cisplatin was used triple-negative breast cancer cell lines (MDA-MB-231, MDA-MB-436, MDA-MB-468 and HCC-1937), cervical cancer cell lines (ME-180 and SiHa) and lung cancer cell lines (A549 and H460). The physico-chemical characterization showed the formation of the inclusion complex in solid and aqueous state and with a molar ratio between the ERL and HP--CD preferably 1:1. Phase-solubility analysis showed AL-type diagrams and the isothermal titration calorimetry and nuclear Overhauser effect spectroscopy support that formation. Cytotoxicity assays showed a higher cytotoxicity of inclusion complex (ERL:HP--CD) in relation to the free ERL (37.5 M), which can be explained by increase in solubility of ERL by HP--CD. Furthermore, the ERL and inclusion complex ERL:HP--CD showed higher cytotoxicity to tumor cells (A431 and Caco-2) than to normal cell (osteoblasts). In addition, the inclusioncomplex exhibited antiangiogenic activity without affect the activation andrecruitment of neutrophils and macrophages. Thus, the results suggest that the inclusion complex (ERL:HP--CD) may be used for the development of ERLbased formulations. With regard the effect of hyperthermia, heat was cytotoxicity in 3 of the 4 breast cancer cell lines evaluated (MDA-MB-231, MDAMB- 436 and MDA-MB-468) and in 2 cervical cancer cell lines (ME-180 and SiHa), this being more evident on 43°C. The lung cancer cells were resistant to heat. Furthermore, the heat changed the cisplatin value of 50% inhibitory concentration (IC50) in MDA-MB-231 and MDA-MB-436 cells. Hyperthermia showed cytotoxic activity for tumor cells, but should be used with a criterion, because certain cells exhibit resistance to the temperature increase.